Sustainable energy transition challenges in selected ASEAN countries: a 4A framework and data envelopment analysis perspective / Umme Humayara Manni and Kasim Md. Mansur - Manni, Umme Humayara; Md. Mansur, Kasim (Universiti Teknologi MARA, Perak, 2024)
Energy security—considering depleting fossil fuel sources, growing energy demand, the availability and affordability of renewables, and the environmental effects of energy production and consumption is a significant issue for all governments. The research examines the 2010–2021 ASEAN energy transition hurdles. The 4A framework statistically monitored availability, acceptability, affordability, and application, while the DEA approach assessed renewable energy sustainability. Oil, gas, and coal reserve-production ratios, energy intensity, CO2 emissions, renewable energy, fossil fuel subsidies, and GDP per capita are indicators. The 4A paradigm depicts countries regressing on availability and affordability while maintaining application and acceptability. The DEA technique suggests using renewable energy to enhance productivity and reduce CO2 emissions in developed nations. The suggested DEA technique uses renewable energy consumption, total energy consumption, labor, natural resource rent, and installed renewable capacity as inputs and GDP and CO2 emissions as outputs to prioritize economic or environmental criteria in sustainable development evaluations. All nations except Vietnam have comparable 2010 GDP and CO2 emissions. CO2 consumption increased Vietnam’s GDP and decreased in the Philippines in 2015. The input suggests that policymakers prioritize energy policy assessment and development utilizing the 4A framework and DEA methodology. Policymakers should also examine inventive ways to promote renewable energy and deliver cheap, low-carbon power. ASEAN should also address pricing, energy imports, and energy use’s environmental and climate change implications to hasten the low-carbon energy transition. The research emphasizes economic development but may miss renewable energy’s political and economic effects. Future studies should examine ASEAN renewable energy hurdles and their economic, social, and employment effects.